Genetic and anatomic relationships among three morphotypes of the echinoid Echinocrepis rostrata - Vardaro, Michael F (INVERTEBRATE BIOLOGY, 2010)
Three morphotypes-purple, tan, and white-of an irregular echinoid of the genus Echinocrepis are commonly observed in the deep North Pacific Ocean. Mitochondrial (mt) 16S DNA and cytochrome c oxidase subunit I (COI) DNA sequences were amplified from gonadal tissue samples from specimens of each morphotype. These portions of the mitochondrial genome are commonly used in species barcoding, and their similarities were compared and placed in 95{%} connection limit parsimony networks. All three morphotypes have similar 16S mtDNA and COI mtDNA sequences, and are thus likely representatives of the same species, Echinocrepis rostrata. Specimens of the white morphotype were smaller than the specimens of the other two morphotypes, had less gonad tissue, and had a different body shape, suggesting that it represents the juvenile form of E. rostrata. Resolving the three morphotypes into one species simplifies the identification of E. rostrata from photographs and leads to a greater understanding of the life history and reproductive cycle of a species vital to deep-sea bioturbation and carbon sequestration.
Keywords: HOV Alvin (Human Occupied Vehicle); ROV Jason (Remotely Operated Vehicle)